2022
DOI: 10.3390/bs13010035
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Mild, Moderate, and Severe Nomophobia Symptoms: A Systematic Review, Meta-Analysis, and Meta-Regression

Abstract: NOMOPHOBIA, or NO MObile PHone Phobia, refers to a psychological condition in which people fear being disconnected from their mobile phones. The purpose of this review was to establish the prevalence of nomophobia symptoms in youth and young adults according to severity, country, culture, population, measurement tool, and year of data collection. An electronic search of fourteen databases, two digital preservation services, and three content aggregator services was conducted from the inception of each database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 90 publications
0
18
0
2
Order By: Relevance
“…Regarding the rst nding, although epidemiologic surveys of depressive and anxiety symptoms among university students have been conducted, the results have been inconsistent. For example, the metaanalysis by Jahrami et al reported a global prevalence of 32.5% for both depression and anxiety among students [49], while Martínez-Líbano et al reported percentages of 63.1% and 69.2% for depression and anxiety [50], respectively. Ramón-Arbués et al reported results of 3.8% and 24.5% for depressive and anxiety symptoms, respectively, among students [33].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the rst nding, although epidemiologic surveys of depressive and anxiety symptoms among university students have been conducted, the results have been inconsistent. For example, the metaanalysis by Jahrami et al reported a global prevalence of 32.5% for both depression and anxiety among students [49], while Martínez-Líbano et al reported percentages of 63.1% and 69.2% for depression and anxiety [50], respectively. Ramón-Arbués et al reported results of 3.8% and 24.5% for depressive and anxiety symptoms, respectively, among students [33].…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence from another recent meta-analysis that shows that most people have mild or moderate symptoms, with mild, moderate, and severe symptoms being present in 25%, 50%, and 20%, respectively [ 43 ]. Severe symptoms are most common among university students from non-Western cultures and countries [ 43 ]. The year 2021 saw an increase in the prevalence of nomophobia, which could be linked to COVID-19 [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Severe symptoms are most common among university students from non-Western cultures and countries [ 43 ]. The year 2021 saw an increase in the prevalence of nomophobia, which could be linked to COVID-19 [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, financially literate investors were also influenced by behavioral biases (Rieger et al, 2022a;Iram et al, 2023;Jonsson et al, 2017). In another research study, fear of missing out (FOMO) emerged as a novel behavioral bias to affect the investment decision-making process of investors (Gupta and Shrivastava, 2022;Jahrami et al, 2022;Shiva et al, 2020). These behavioral biases were garnered from the existing market structure and related parameters to affect the investors' decision-making abilities (Jain et al, 2022;Iram et al, 2023;Jahrami et al, 2022;Shiva et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…, 2017). In another research study, fear of missing out (FOMO) emerged as a novel behavioral bias to affect the investment decision-making process of investors (Gupta and Shrivastava, 2022; Jahrami et al. , 2022; Shiva et al.…”
Section: Introductionmentioning
confidence: 99%